Supportive treatment for cast nephropathy in patients with multiple myeloma; a pilot study - Giovanni Cancarini; Vincenzo Terlizzi; Anna Garatti; Letizia Zeni; Mattia Tonoli; Elena Pezzini; Francesca Boni; Stefano Possenti; Battista Fabio Viola; Mario Gaggiotti (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Cast nephropathy is a prevalent cause of acute kidney injury (AKI) in patients with myeloma. Objectives: The aim of this study is to define the outcome of a standardized supportive therapy for cast nephropathy. Patients and Methods: Retrospective analysis of the outcome of cast nephropathy in a University hospital for a period of five years. Data analysed; serum creatinine, estimated glomerular filtration rate (eGFR; mL/min/1.73 m2 BSA) and need for dialysis. Standardized therapy with the aim of preventing/removing tubular casts; fluid administration and mannitol to increase urine flow, sodium bicarbonate to alkalize the urine and low dose steroid to reduce peritubular inflammation. Statistical analysis: Student's t-test or the Mann-Whitney test according to data distribution. A two-tailed P value <0.05 was considered statistically significant. Survival curve was drawn according to Kaplan and Meier. Results: Twenty-seven cases were reviewed. Upon admission, mean serum creatinine was 7.1±4.9 mg/dL and mean eGFR 6±4 mL/min/1.73 m2 BSA; 30% of patients had oligo-anuria. Diagnosis of cast nephropathy was presumptive in 23 patients, and renal biopsy proven in four. Hemodialysis was required by 10 (37%) patients, two of whom continued dialysis after discharge. At discharge, serum creatinine was 3.7±2.5 mg/dL and eGFR 20±13 mL/min/1.73 m2 BSA (P=0.002), and after a median of 3.4 months, the values were 2.9±2.1 mg/dL and 35±32 mL/min/1.73 m2 BSA, respectively. Patient survival was 60% after 24 months. Conclusion: Administration of fluid, mannitol, sodium bicarbonate and low-dose steroid may improve the outcome of cast nephropathy. Despite the fact that the study has many limitations, its findings could be the base for prospective controlled trials on cast nephropathy and could be useful in those countries where the expensive extracorporeal treatments are not available.